Application of Media Political Economic Theory in The Kick Andy Program on Metro TV with Childfree Theme - Fitria, Namira (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
The phenomenon regarding Childfree has now become a Viral and Trending Topic on social media. Childfree itself is a decision for married couples who decide not to have children in their household. This decision is being widely discussed so that when this issue is broadcast on television media it has the opportunity to get high ratings. This research aims to analyze editorial in commodifying the content (commodification of content) of an event into an interesting show that is worth broadcasting and worth selling to produce a profit for the company. This research method uses a qualitative approach, with a constructivist paradigm and uses data collection methods through observation. The findings from this research are the commodification of content or issues regarding childfree. There are political economic interests carried out by capital owners so if we look at it from this point of view, it can be seen as something that was born because of the domination of one group over another group in the form of control for profit and being a capitalist agent. It is hoped that the implications of this research can enrich case studies regarding the political economy of the media. Thus, in the future the viewing public will be "media aware" and the media can be utilized as fully as possible, not only from a commercial perspective.